Housing preference for tenement rental housing of low-income renters in informal areas in Davao City - Aznar, Dax Raymond S.; Orendain, Dan Jezreel A. (2017)
The study aims to profile and evaluate existing rental housing in informal areas and to conduct a survey on the rental housing preference of low-income renters. The result showed that in the existing rental housing in informal areas, there are four space configurations that was observed, each of this configuration caters to different needs of low-income renters. Two approaches of preference research was used, the revealed preference and the stated-preference approach. In the revealed preference approach, it showed that affordable rental rates, safety, a clean environment and access to the central district are most influential factors in rental housing. While in the stated preference approach, it showed that renters would trade-off having a good sized rental unit in order to be situated in or near the central district of a city and have affordable rental rates. The study area is only focused to one barangay thus it is recommended to have a broader study area and parameters in terms of rental housing. The general data in the study shows existing state of rental housing and the preference of low-income renters, these can be used as a good basis in creating a viable rental housing development that caters to the needs of the urban poor.
Thesis (BS Architecture) -- University of the Philippines Mindanao, June 2017